EFFECT OF ORGANISATIONAL DYNAMICS ON ACCOUNTING PRACTICES OF LISTED DEPOSIT MONEY BANKS (DMBs) IN NIGERIA - Mubaraq Sanni (Malete Journal of Accounting and Finance)
Accounting scandals and financial irregularities have always been conducted to achieve numerous objectives which however become cancerous issues truncating the survival of firms. The nature and level of damage arising from accounting scandals and financial irregularities differ based on individual firm characteristics. Hence, this study examined the effect of organisational dynamics on accounting practices of listed deposit money banks in Nigeria. This study adopts ex-post facto research design and data was sourced from 13 out of 14 listed deposit money banks as at 2018. The generalised moment model regression model technique was used and the result showed that profitability has positive significant effect on accounting practice of deposit money in Nigeria; foreign listing has no significant effect on accounting practice of deposit money banks in Nigeria; and, leverage has positive significant effect on accounting practice of deposit money banks in Nigeria. The study concluded that organisation dynamics contributes significantly to accounting practice of deposit money banks in Nigeria. The study therefore recommended that profitability decision should be considered more by Nigerian deposit money bank in order to reduce accounting practice and to measure board performance.